Umur dan Jenis Kelamin Kucing Penderita Feline Panleukopenia - Indarjulianto, Soedarmanto; Daniswari, Priyanka Primananda; Nugroho, Fatah; Airin, Claude Mona; Yanuartono, Yanuartono; Paryuni, Alsi Dara (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2025)
Feline Panleukopenia (FP) is an infectious disease caused by a virus that still often attacks cats of all ages and sex. This study aims to study the age and sex of cats suffering from feline panleukopnia. This study used 16 cats of all ages and sex that showed clinical signs of FP. All cats were examined clinically and blood samples were checked for total leukocytes. The results showed that all cats had leukopenia, so they were diagnosed with FP. The cats suffering from FP consisted of 3/16 cats (18.75%) < 7 months old, 9/16 cats (56.25%) 7-12 months old and 4/16 cats (25%) >12 months old. Based on sex, cats consist of 10/16 males (62.5%) and 6/16 females (37.5%). Based on this research, it was concluded that feline panleukopenia is more common in cats aged ≤12 months and male cats.